Preparation method of aramid nanofiber film-aerogel complex

By integrating BNNS, MXene, and AgNWs, the method addresses dispersion and thermal conductivity issues in ANF gasolines, resulting in a high-performance composite for flexible electronics and smart sensors.

CN120310052APending Publication Date: 2025-07-15KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510606530.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-12
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

The existing aramid nanofiber aerogels have shortcomings in dispersion, mechanical stability, conductivity and thermal management capabilities, which are difficult to meet the needs of flexible sensing and smart materials, and the interface binding force is insufficient, making them easy to peel off in complex environments.

Method used

By introducing boron nitride nanosheets (BNNS), two-dimensional materials MXene obtained by peeling off titanium aluminum carbide, and silver nanowires AgNWs, the interface binding force and heat conduction path are optimized, and aramid nanofiber film-aerogel composites are prepared.

Benefits of technology

It significantly improves the mechanical properties, conductivity and structural stability of the composite, improves the sensing sensitivity and response speed, alleviates the problem of heat accumulation, enhances the interface bonding strength and heat dissipation performance, and is suitable for stable applications in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method of an aramid nanofiber film-aerogel complex, and belongs to the technical field of high-performance composites.The preparation method comprises the steps that an aramid nanofiber film and aramid nanofiber film-based aerogel are compounded, filler such as boron nitride nanosheets and silver nanowires is introduced, the interface bonding force and the heat management capacity are optimized, and the thermal conductivity of the composite is improved; the complex with excellent impact resistance, heat dissipation performance and cold insulation / heat insulation performance is prepared; the problems that traditional aerogel is poor in structural stability and serious in heat accumulation are solved, and the aerogel can be widely applied to the fields of thermal protection, energy storage, electromagnetic shielding, flexible electronics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-performance composite materials, and specifically to a preparation method of an aramid nanofiber film-aerogel composite. Background Art

[0002] In recent years, due to their unique ultra-low density, high porosity and excellent specific surface area, aerogel materials have shown broad application prospects in the fields of energy storage, environmental governance, thermal management and flexible electronics. Among them, aramid nanofiber (ANF) aerogels have become a research hotspot of high-performance functional aerogels due to their excellent high-temperature resistance, mechanical strength and chemical stability. However, ANF aerogels still face many challenges in practical applications: on the one hand, due to the strong intermolecular hydrogen bond interaction of ANF, it is difficult to disperse uniformly in the solution, resulting in non-uniform aerogel structure and insufficient mechanical stability; on the other hand, the inherent electrical insulation property of ANF limits its application in the fields of flexible sensing and intelligent materials, and it is difficult to meet the requirements of modern electronic devices for conductivity and functional diversification.

[0003] The traditional modification methods of ANF aerogels mainly rely on single-component optimization. For example, the dispersibility is improved by polyvinyl alcohol (PVA) or the conductivity is increased by conductive fillers. However, these strategies often struggle to balance mechanical properties, structural stability and functional characteristics. In addition, the low thermal conductivity of aerogels easily leads to local heat accumulation, accelerating material aging and further shortening its service life. Therefore, how to improve its interfacial bonding force, thermal management ability and conductivity while maintaining the lightweight porous structure of the aerogel has become the core issue of current research.

[0004] In response to the above problems, scholars at home and abroad have actively explored composite modification strategies. For example, introducing boron nitride nanosheets (BNNS) can optimize the heat conduction path of the aerogel and alleviate the heat accumulation problem; the addition of two-dimensional material MXene and highly conductive silver nanowires (AgNWs) can construct an efficient conductive network, endowing the aerogel with excellent sensing performance. However, existing research mostly focuses on single-functional modification, lacking a systematic study of the synergistic action mechanism of materials, resulting in limited improvement in the comprehensive performance of composite aerogels. In addition, the insufficient interfacial bonding force between the aerogel and the protective layer is prone to peeling in complex environments, further restricting its practical application.

[0005] Therefore, developing an ANF-based composite aerogel with high mechanical strength, excellent thermal management ability and conductive characteristics, and realizing its stable composite with functional films is of great significance for promoting the application of aerogel materials in the fields of flexible electronics, intelligent sensing, etc. Summary of the Invention

[0006] Through multi-component collaborative regulation and interface optimization design, the present invention aims to solve the above technical problems and provide new ideas for the preparation of high-performance aerogel composites. A preparation method of an aramid nanofiber film-aerogel composite, by introducing fillers such as boron nitride nanosheets (BNNS), two-dimensional material MXene obtained by exfoliating aluminum titanium carbide, and silver nanowires AgNWs, optimizes the interfacial bonding force and heat conduction path to prepare a high-performance composite.

[0007] The technical solution of the present invention is as follows: A preparation method of an aramid nanofiber film-aerogel composite, comprising the following steps: (1) Place the ANF film in a glass petri dish, place the hollow mold on the upper surface of the ANF film, add the ANF / dimethyl sulfoxide dispersion into the hollow mold, and let it stand to form interfacial adhesion; (2) Add deionized water to the glass petri dish, allow the ANF / dimethyl sulfoxide dispersion in the hollow mold to undergo an ionization reaction from the edge to the inside for a period of time, then extract the deionized water in the glass petri dish, and re-add deionized water, repeat until no more dimethyl sulfoxide (DMSO) precipitates in the deionized water to obtain the ANF film-hydrogel composite; (3) Directionally freeze the ANF film-hydrogel composite in a liquid nitrogen environment, and then freeze-dry it to obtain the ANF film-aerogel composite.

[0008] In step (1), the mass fraction of the ANF / dimethyl sulfoxide dispersion is 1-3%.

[0009] In step (2), the deionized water in the glass petri dish is extracted after the ionization reaction for 12-24 h.

[0010] In step (3), freeze-drying is carried out at -3.6±0.5 °C and a pressure ≤5 Pa for more than 36 h.

[0011] Replace the ANF film in step (1) with an ANF / BNNS film, and replace the ANF / dimethyl sulfoxide dispersion with a dimethyl sulfoxide mixture of ANF / PVA / MXene / AgNWs, and keep other steps unchanged to prepare the ANF / BNNS film-ANF / PVA / MXene / AgNWs aerogel composite.

[0012] The ANF / BNNS film is formed by pressing after mixing ANF and the BNNS film, wherein the mass fraction of BNNS is 20-40%.

[0013] In the ANF / PVA / MXene / AgNWs mixture, the mass fraction of ANF is 1 - 3%, the mass fraction of PVA is 0.2 - 0.6%, the mass fraction of MXene is 0.6 - 1%, and the mass fraction of AgNWs is 0.1 - 0.3%; MXene is a two-dimensional material obtained by exfoliating aluminum titanium carbide; AgNWs are silver nanowires with a length of 10 - 50 μm and a diameter of 20 - 100 nm.

[0014] Advantages of the present invention: 1. By introducing multifunctional fillers such as PVA, MXene, and AgNWs, the present invention synergistically optimizes the mechanical properties, electrical conductivity, and structural stability of the ANF aerogel. Among them, PVA effectively inhibits the shrinkage of the aerogel, and MXene and AgNWs construct an efficient conductive network, significantly improving the sensing sensitivity and response speed of the composite, making it have broad application prospects in the fields of flexible electronics and intelligent sensing.

[0015] 2. The present invention uses the ANF / BNNS composite film as a protective layer, and combines the dissolution-reconstruction mechanism promoted by BNNS to significantly improve the interfacial bonding strength between the film and the aerogel. At the same time, the high thermal conductivity network formed by the synergy of BNNS and MXene effectively alleviates the heat accumulation problem of the aerogel, improves the heat dissipation performance of the composite, and extends its service life in high-temperature environments; 3. The composite prepared by the present invention has excellent impact resistance and cold / heat insulation capabilities. The film layer effectively disperses the impact stress and protects the structural integrity of the aerogel, while the optimized pore structure and filler distribution enhance the temperature buffering effect, enabling the material to maintain stable performance in extreme environments (such as high temperature, low temperature, or mechanical shock), and being suitable for demanding application scenarios such as aerospace, military protection, and intelligent wear. Description of the drawings

[0016] Figure 1 are the microstructures of the aerogel and the film; Figure 2 are the infrared spectra of aerogels with different MXene and AgNWs contents; Figure 3 are the infrared spectra of ANF / BNNS composite films with different BNNS addition amounts; Figure 4 is the microstructure at the interface of the ANF / BNNS film - ANF / PVA / MXene / AgNWs aerogel composite; Figure 5 is the comparison chart of the thermal conductivity of the ANF / BNNS film - ANF / PVA / MXene / AgNWs aerogel composite and the aerogel; Figure 6 It is a comparison chart of the cold insulation / heat insulation performance of the ANF / BNNS thin film - ANF / PVA / MXene / AgNWs aerogel composite and the aerogel. Specific implementation manners

[0017] The following further describes the present invention in detail with reference to specific embodiments. It should be noted that the protection scope of the present invention is not limited by these embodiments. The aramid short fibers used in the embodiments of the present invention are all from Hebei Silicon Valley Chemical Co., Ltd. MXene is a two-dimensional material obtained by exfoliating aluminum titanium carbide; AgNWs are silver nanowires with a length of 10 - 50 μm and a diameter of 100 - 200 nm.

[0018] Example 1

[0019] Preparation method of ANF / dimethyl sulfoxide dispersion: Dissolve 10 g of KOH in 6 mL of deionized water, then add 10 g of aramid short fibers and 500 g of DMSO to the above mixture, and stir with a mechanical stirring device at 25°C for 72 h to obtain a 2 wt% ANF / dimethyl sulfoxide dispersion.

[0020] Prepare a 1 wt% ANF / dimethyl sulfoxide dispersion and a 3 wt% ANF / dimethyl sulfoxide dispersion respectively according to the method of Example 1.

[0021] Example 2

[0022] Preparation method of ANF thin film: Take 25 g of a 2 wt% ANF / dimethyl sulfoxide dispersion, add 50 mL of H2O, and continuously stir during the addition process to completely protonate the ANF. Subsequently, pour the completely protonated gel-like solution into a juicer blender and stir for 1 min. After the stirring is completed, pour the suspension into a sintered filter device and connect a circulating water vacuum pump for suction filtration. During the suction filtration process, continuously add H2O to remove KOH and DMSO in the suspension. After the suction filtration is completed, transfer the filter paper and the mixture on the paper to a hydraulic press and press for 5 min, and then transfer it to a paper sheet and quickly dry it in a dryer for 20 min to obtain an ANF thin film.

[0023] Different ANF thin films can also be prepared using a 1 wt% ANF / dimethyl sulfoxide dispersion and a 3 wt% ANF / dimethyl sulfoxide dispersion.

[0024] Example 3

[0025] Preparation method of ANF / PVA / MXene / AgNWs dimethyl sulfoxide mixed solution: Add PVA to DMSO, place the suspension in a water bath at 70 °C and heat it for dissolution for 30 min. Wait until PVA is completely dissolved in DMSO (i.e., the suspension becomes colorless and transparent), mix it with a 2 wt% ANF / dimethyl sulfoxide dispersion, shake well to form an ANF / PVA mixture, then add MXene and AgNWs, shake for 20 min until MXene and AgNWs are evenly dispersed in the ANF / PVA mixture (the judgment criterion is that the color of the mixture is uniformly dark green) to obtain an ANF / PVA / MXene / AgNWs mixture.

[0026] Adjust the dosage of each raw material as needed so that the mass fraction of PVA in the ANF / PVA / MXene / AgNWs mixture is 0.2 - 0.6%, the mass fraction of MXene is 0.6 - 1%, and the mass fraction of AgNWs is 0.1 - 0.3%.

[0027] Example 4

[0028] Preparation method of ANF / BNNS film: Take 25 g of a 2 wt% ANF / dimethyl sulfoxide dispersion, add 2.5 mg of BNNS, place it in an ultrasonic cleaner and ultrasonicate for 3 min to uniformly mix BNNS and ANF. After ultrasonication, add 50 mL of water, and continuously stir during the addition process to completely protonate ANF. Then pour the completely protonated gel-like product into a juicer blender and stir for 1 min. After stirring, pour the above suspension into a sand core filtration device and connect a circulating water vacuum pump for suction filtration. Continuously add water during the suction filtration process to remove KOH and DMSO in the suspension. After suction filtration, transfer the filter paper and the mixture on the paper to a hydraulic press and press for 5 min, then transfer it to a paper sheet rapid dryer and dry for 20 min to obtain an ANF / BNNS composite film with a BNNS content of 10 wt%.

[0029] According to the method of Example 4, add 5, 7.5, and 10 mg of BNNS respectively, keep other conditions unchanged, and prepare ANF / BNNS composite films with a BNNS content of 20 wt%, ANF / BNNS composite films with a BNNS content of 30 wt%, and ANF / BNNS composite films with a BNNS content of 40 wt% respectively.

[0030] Example 5

[0031] A preparation method of an ANF film-aerogel composite, the specific steps are as follows: (1) Place an ANF film with a diameter of 3.5 cm (prepared from a 2 wt% ANF / dimethyl sulfoxide dispersion) in a 10 cm × 10 cm × 2 cm glass petri dish. Closely attach a 2.5 cm × 2.5 cm × 2.5 cm rubber mold above it. Add 4 g of a 1% ANF / dimethyl sulfoxide dispersion into the mold and let it stand for 24 h to allow the ANF to fully deposit and form an interfacial adhesion with the film below. (2) Add 20 mL of deionized water to the glass petri dish to initiate the ionization reaction of the ANF in the mold from the edge to the inside. After 12 h, use a 50 mL syringe to extract the water and the displaced DMSO in the petri dish, and then re-inject 20 mL of deionized water. Repeat the water replacement 3 times, and then increase the water replacement frequency to once every 4 h until no DMSO precipitation is detected, completing the protonation reaction. (3) Remove the mold to obtain the ANF film-hydrogel composite. Place this composite on the top of a 10 cm × 10 cm × 10 cm sealed copper box, fill it with liquid nitrogen, seal it, and freeze it for 10 min to achieve uniform freezing of the internal structure. (4) Transfer the frozen composite to a vacuum freeze dryer and freeze-dry it for 36 h at -3.6 ± 0.5 °C and a pressure ≤ 5 Pa to completely sublime the water, obtaining a structurally complete ANF film-aerogel composite.

[0032] Example 6

[0033] A method for preparing an ANF film-aerogel composite, the specific steps are as follows: (1) Place an ANF film with a diameter of 3.5 cm (prepared from a 3 wt% ANF / dimethyl sulfoxide dispersion) in a 10 cm × 10 cm × 2 cm glass petri dish. Closely attach a 2.5 cm × 2.5 cm × 2.5 cm rubber mold above it. Add 4 g of a 1% ANF / dimethyl sulfoxide dispersion into the mold and let it stand for 24 h to allow the ANF to fully deposit and form an interfacial adhesion with the film below. (2) Add 20 mL of deionized water to the petri dish to initiate the ionization reaction of the ANF in the mold from the edge to the inside. After 24 h, use a 50 mL syringe to extract the water and the displaced DMSO in the petri dish, and then re-inject 20 mL of deionized water. Repeat the water replacement 3 times, and then increase the water replacement frequency to once every 4 h until no DMSO precipitation is detected, completing the protonation reaction. (3) Remove the mold to obtain the ANF film-hydrogel composite. Place this composite on the top of a 10 cm × 10 cm × 10 cm sealed copper box, fill it with liquid nitrogen, seal it, and freeze it for 10 min to achieve uniform freezing of the internal structure. (4) Transfer the frozen composite to a vacuum freeze dryer and freeze-dry it for 36 h under the conditions of -3.6 ± 0.5 °C and a pressure ≤ 5 Pa to completely sublime the moisture and obtain a structurally complete ANF film-aerogel composite.

[0034] Example 7

[0035] A preparation method of an ANF film-aerogel composite, the specific steps are as follows: (1) Place an ANF film with a diameter of 3.5 cm (prepared from a 1 wt% ANF / dimethyl sulfoxide dispersion) in a 10 cm × 10 cm × 2 cm glass petri dish, closely attach a 2.5 cm × 2.5 cm × 2.5 cm rubber mold above it, add 4 g of a 1% ANF / dimethyl sulfoxide dispersion to the mold, and let it stand for 24 h to allow the ANF to fully deposit and form an interfacial adhesion with the film below; (2) Add 20 mL of deionized water to the petri dish to cause the ANF in the mold to undergo an ionization reaction from the edge to the inside. After 18 h, use a 50 mL syringe to extract the water and the displaced DMSO in the petri dish, and re-inject 20 mL of deionized water. Repeat the water change 3 times, and then increase the water change frequency to once every 4 h until no DMSO precipitation is detected to complete the protonation reaction; (3) Remove the mold to obtain an ANF film-hydrogel composite, place the composite on the top of a 10 cm × 10 cm × 10 cm sealed copper box, fill it with liquid nitrogen, seal it, and freeze it for 10 min to uniformly freeze the internal structure; (4) Transfer the frozen composite to a vacuum freeze dryer and freeze-dry it for 40 h under the conditions of -3.6 ± 0.5 °C and a pressure ≤ 5 Pa to completely sublime the moisture and obtain a structurally complete ANF film-aerogel composite.

[0036] Example 8

[0037] A preparation method of an ANF / BNNS film-ANF / PVA / MXene / AgNWs aerogel composite, the specific steps are as follows: (1) Place an ANF / BNNS film with a diameter of 3.5 cm (the content of BNNS in the film is 20%) in a 10 cm × 10 cm × 2 cm glass petri dish, closely attach a 2.5 cm × 2.5 cm × 2.5 cm rubber mold above it, add 4 g of an ANF / PVA / MXene / AgNWs mixture to the mold, where the mass fractions of ANF, PVA, MXene, and AgNWs are 1%, 0.2%, 0.6%, and 0.1% respectively, and let it stand for 24 h to allow the ANF to fully deposit and form an interfacial adhesion with the film below; (2) Add 20 mL of deionized water to the petri dish to cause the ionization reaction of the ANF / PVA / MXene / AgNWs mixture in the mold from the edge to the inside. After 12 h, use a 50 mL syringe to extract the water and the displaced DMSO in the petri dish, and re-inject 20 mL of deionized water. Repeat the water replacement 3 times, and then increase the water replacement frequency to once every 4 h until no DMSO precipitation is detected, thus completing the protonation reaction; (3) Remove the mold to obtain the ANF film-hydrogel composite. Place the composite on the top of a sealed copper box of 10 cm × 10 cm × 10 cm, fill it with liquid nitrogen, seal it, and freeze it for 10 min to achieve uniform freezing of the internal structure; (4) Transfer the frozen composite to a vacuum freeze dryer and freeze-dry it for 36 h under the conditions of -3.6 ± 0.5 °C and a pressure ≤ 5 Pa to completely sublimate the water, thus obtaining a structurally complete ANF film-ANF / PVA / MXene / AgNWs aerogel composite.

[0038] Example 9

[0039] A preparation method of an ANF / BNNS film-ANF / PVA / MXene / AgNWs aerogel composite, the specific steps are as follows: (1) Place an ANF / BNNS film with a diameter of 3.5 cm (the content of BNNS in the film is 30%) in a glass petri dish of 10 cm × 10 cm × 2 cm, and closely fit a rubber mold of 2.5 cm × 2.5 cm × 2.5 cm above it. Add 4 g of ANF / PVA / MXene / AgNWs mixture to the mold, where the mass fractions of ANF, PVA, MXene, and AgNWs are 2%, 0.4%, 0.8%, and 0.2% respectively, and let it stand for 24 h to allow ANF to fully deposit and form an interfacial adhesion with the lower film; (2) Add 20 mL of deionized water to the petri dish to cause the ionization reaction of the ANF / PVA / MXene / AgNWs mixture in the mold from the edge to the inside. After 18 h, use a 50 mL syringe to extract the water and the displaced DMSO in the petri dish, and re-inject 20 mL of deionized water. Repeat the water replacement 3 times, and then increase the water replacement frequency to once every 4 h until no DMSO precipitation is detected, thus completing the protonation reaction; (3) Remove the mold to obtain the ANF film-hydrogel composite. Place the composite on the top of a sealed copper box of 10 cm × 10 cm × 10 cm, fill it with liquid nitrogen, seal it, and freeze it for 10 min to achieve uniform freezing of the internal structure; (4) Transfer the frozen composite to a vacuum freeze dryer and freeze-dry it for 36 h under the conditions of -3.6 ± 0.5 °C and a pressure ≤ 5 Pa to completely sublime the moisture, obtaining a structurally complete ANF / BNNS film-ANF / PVA / MXene / AgNWs aerogel composite.

[0040] Example 10

[0041] A preparation method of an ANF / BNNS film-ANF / PVA / MXene / AgNWs aerogel composite, the specific steps are as follows: (1) Place an ANF / BNNS film with a diameter of 3.5 cm (the content of BNNS in the film is 40%) in a 10 cm × 10 cm × 2 cm glass petri dish, closely attach a 2.5 cm × 2.5 cm × 2.5 cm rubber mold above it, and add 4 g of ANF / PVA / MXene / AgNWs mixed solution into the mold, where the mass fractions of ANF, PVA, MXene, and AgNWs are 3%, 0.6%, 1%, and 0.3% respectively, and let it stand for 24 h to fully deposit the mixed solution and form an interfacial adhesion with the lower film; (2) Add 20 mL of deionized water to the petri dish to carry out an ionization reaction of the ANF / PVA / MXene / AgNWs mixed solution in the mold from the edge to the inside. After 12 h, use a 50 mL syringe to extract the water and the displaced DMSO in the petri dish, and re-inject 20 mL of deionized water. Repeat the water change 3 times, and then increase the water change frequency to once every 4 h until no DMSO precipitation is detected, completing the protonation reaction; (3) Remove the mold to obtain an ANF / BNNS film-ANF / PVA / MXene / AgNWs hydrogel composite. Place the composite on the top of a 10 cm × 10 cm × 10 cm sealed copper box, fill it with liquid nitrogen, seal it, and freeze it for 10 min to uniformly freeze the internal structure; (4) Transfer the frozen composite to a vacuum freeze dryer and freeze-dry it for 36 h under the conditions of -3.6 ± 0.5 °C and a pressure ≤ 5 Pa to completely sublime the moisture, obtaining a structurally complete ANF / BNNS film-ANF / PVA / MXene / AgNWs aerogel composite.

[0042] According to the method of Example 10, change the mass fractions of ANF, PVA, MXene, and AgNWs in the ANF / PVA / MXene / AgNWs mixture to (3%, 0%, 0%, 0.5%), (3%, 0.6%, 1%, 0.5%), (3%, 0.6%, 2%, 0.5%), (3%, 0.6%, 3%, 0.5%), (3%, 0.6%, 4%, 0.5%), (3%, 0.6%, 5%, 0.5%), (3%, 0.6%, 5%, 1%), and prepare ANF / BNNS film-ANF / PVA / MXene / AgNWs aerogel composites respectively.

[0043] Comparative Example 1 Preparation method of aerogel: Place a 2.5 cm×2.5 cm×2.5 cm rubber mold in a 10 cm×10 cm×2 cm glass petri dish. Quickly add 4 g of the ANF / PVA / MXene / AgNWs mixture (where the mass fractions of ANF, PVA, MXene, and AgNWs are 2%, 0.4%, 0.8%, and 0.2% respectively) into the mold, and add 20 mL of deionized water to the petri dish to gradually ionize the ANF in the mold from the edge to the inside. After 18 h, use a 50 mL syringe to draw out the water and the displaced DMSO in the petri dish, and re-inject 20 mL of deionized water. Repeat the above process 3 times, and then increase the water change frequency to once every 4 h until no DMSO precipitation is observed during water change, indicating that the protonation reaction has occurred completely. Finally, the gel formed in the mold is the ANF / PVA / MXene / AgNWs hydrogel. Place the above obtained hydrogel on top of a sealed copper box (size: 10 cm×10 cm×10 cm), fill the box with liquid nitrogen and seal the lid. Using the bottom-up directional freezing technique, freeze the hydrogel in the liquid nitrogen environment for 10 min to form a porous frozen gel. Subsequently, transfer the obtained frozen gel to a vacuum freeze dryer for freeze drying. During the freeze drying process, the sample temperature is maintained at -3.6±0.5 °C, the chamber pressure is maintained at 5 Pa or below, and the freeze drying time is set to 36 h to ensure that the water in the frozen gel is completely sublimated. After the freeze drying is completed, the ANF / PVA / MXene / AgNWs aerogel is obtained.

[0044] Figure 1Microstructures of the ANF film prepared in Example 4 (below) and the aerogel prepared in Comparative Example 1 (above). As can be seen from the figure, the aerogel exhibits a highly dispersed and uniform three-dimensional nanofiber network. The fibers are intertwined to form a relatively regular pore structure, and the overall porosity is relatively high. This hierarchical pore structure not only endows the aerogel with ultra-light characteristics but also provides a large specific surface area. The surface of the ANF / BNNS20 composite film is relatively flat, and there is an obvious embedded structure of white BNNS particles. Figure 2 Infrared spectra of aerogels with different MXene and AgNWs contents prepared in Example 10. As can be seen from the figure, the introduction of MXene not only forms characteristic vibration peaks in the region of 600 - 800 cm⁻¹ but also has a certain impact on the intensity or position of the stretching vibration peaks of C=O, C-O, and O-H, indicating that the intermolecular forces inside the material are regulated, and there may be an enhancement of hydrogen bonds, electrostatic interactions, or van der Waals forces between ANF, PVA, and MXene. In addition, the FTIR data also reflect that the introduction of AgNWs does not damage the molecular backbone of ANF, and the composite material still maintains its original aromatic structure. Meanwhile, the chemical stability of the material and its applicability in applications are improved through synergistic effects.

[0045] Figure 3 Infrared spectra of ANF / BNNS composite films with different BNNS addition amounts. As can be seen from the figure, at 3500 - 3300 cm⁻¹, the pure BNNS sample shows obvious stretching vibration absorption peaks of N-H and O-H. In the composite film, the intensity of this peak is enhanced compared to pure ANF, indicating that the addition of BNNS increases the hydrogen bond interaction in the system, which may promote the rearrangement of hydrogen bonds between ANF molecular chains and contribute to improving the solubility and interfacial binding ability of the film. Secondly, near 1650 cm⁻¹, the absorption peak corresponding to the stretching vibration of amide C=O in ANF still exists, and with the increase of BNNS content, the peak position does not shift significantly, indicating that the addition of BNNS does not damage the main chain structure of ANF. However, the change in its peak intensity may reflect the adjustment of intermolecular interactions inside the composite material. In addition, in the range of 1500 - 1000 cm⁻¹, the spectra of ANF / BNNS composite films exhibit multiple characteristic absorption peaks related to B-N bonds. Especially at 1360 cm⁻¹ (B-N-B stretching vibration) and 820 cm⁻¹ (B-N bending vibration), the characteristic absorption peaks of BNNS are still clearly visible in the composite film, indicating the uniform dispersion of BNNS in the composite system.

[0046] Figure 4Microstructure at the interface of the ANF / BNNS film-ANF / PVA / MXene / AgNWs aerogel composite prepared for Example 9. It can be seen from the figure that the interface adhesion between the film and the aerogel is relatively tight, which verifies the feasibility of this method.

[0047] Figure 5 Comparison chart of the cold insulation / heat insulation performance of the ANF / BNNS film-ANF / PVA / MXene / AgNWs aerogel composite and the aerogel prepared for Example 9. It can be seen from the figure that the composite shows more excellent effects in terms of heat insulation and cold insulation performance compared with the aerogel. In the heating experiments (a, c), t1 (heating surface temperature) both rises rapidly, while t2 (unheated surface temperature) shows a larger upward trend in the aerogel (a), while the upward amplitude of t2 in the composite (c) is significantly smaller, indicating that the composite can more effectively inhibit heat transfer and exhibits more excellent heat insulation performance. This improvement may be attributed to the introduction of the film in the composite, forming an additional barrier effect and reducing the effectiveness of the heat conduction path; in the freezing experiments (b, d), t1 (freezing surface temperature) drops rapidly with time, while the downward trend of t2 is more obvious in the aerogel (b), while the decrease of t2 in the composite (d) is relatively slow, indicating that the composite also shows better cold insulation ability in a low-temperature environment. This phenomenon may be due to the uniform structure and the presence of the film at the interface of the composite, which hinders the diffusion of cold to the side without the loaded film, thus delaying the rapid change of temperature.

[0048] Figure 6 Comparison chart of the thermal conductivity of the ANF / BNNS film-ANF / PVA / MXene / AgNWs aerogel composite and the aerogel prepared for Example 9. It can be seen from the figure that the heat dissipation rate of the composite is significantly faster than that of the pure aerogel, manifested as a larger temperature drop amplitude per unit time. At the initial moment, the temperatures of both are similar, 63.3 °C for the aerogel and 64.6 °C for the composite. However, as time goes by, the temperature of the composite drops more rapidly. For example, at 3 s, the temperature of the aerogel is still 48.7 °C, while the composite has dropped to 40.8 °C; at 10 s, the temperature of the aerogel is 29.6 °C, while the composite has dropped to 26.5 °C; after 15 s, the temperature of the composite drops to 20.4 °C, while the aerogel still remains at 23.9 °C, indicating that the heat release efficiency of the composite is higher. This difference in the heat dissipation rate can be attributed to the efficient thermal conduction network constructed by MXene and BNNS at the interface. MXene itself has excellent thermal conductivity, and its two-dimensional sheet structure can form effective heat transfer channels inside the composite material, thereby reducing the interfacial thermal resistance and accelerating heat diffusion. At the same time, the addition of BNNS further optimizes this heat transfer network. The layered structure of BNNS can not only improve the thermal conductivity of the matrix but also cooperate with MXene to enhance the heat transfer efficiency at the interface.

[0049] The specific embodiments of the present invention have been described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the above embodiments, and various changes can be made without departing from the spirit of the present invention within the scope of knowledge possessed by those of ordinary skill in the art.

Claims

1. A preparation method of an aramid nanofiber film-aerogel composite, characterized in that Including the following steps: (1) Place the ANF film in a glass petri dish, place the hollow mold on the upper surface of the ANF film, add the ANF / dimethyl sulfoxide dispersion liquid into the hollow mold, and let it stand for 24 h to form an interfacial adhesion; (2) Add deionized water into the glass petri dish to cause the ANF / dimethyl sulfoxide dispersion liquid in the hollow mold to undergo an ionization reaction from the edge to the inside. Then, extract the deionized water in the glass petri dish and add deionized water again. Repeat until no more dimethyl sulfoxide precipitates in the deionized water to obtain the ANF film-hydrogel composite; (3) Directionally freeze the ANF film-hydrogel composite under a liquid nitrogen environment, and then freeze-dry it to obtain the ANF film-aerogel composite.

2. The preparation method of the aramid nanofiber film-aerogel composite according to claim 1, characterized in that In step (1), the mass fraction of the ANF / dimethyl sulfoxide dispersion liquid is 1-3%.

3. The preparation method of the aramid nanofiber film-aerogel composite according to claim 1, wherein, In step (2), the deionized water in the glass petri dish is extracted after the ionization reaction for 12-24 h.

4. The preparation method of the aramid nanofiber film-aerogel composite according to claim 1, wherein, In step (3), freeze-drying is carried out at -3.6°C and a pressure ≤ 5 Pa for more than 36 h.

5. The preparation method of the aramid nanofiber film-aerogel composite according to claim 1, wherein, Replace the ANF film in step (1) with the ANF / BNNS film, and replace the ANF / dimethyl sulfoxide dispersion liquid with the dimethyl sulfoxide mixed liquid of ANF / PVA / MXene / AgNWs, and keep other steps unchanged to prepare the ANF / BNNS film-ANF / PVA / MXene / AgNWs aerogel composite.

6. The preparation method of the aramid nanofiber film-aerogel composite according to claim 5, characterized in that, The mass fraction of BNNS in the ANF / BNNS film is 20-40%.

7. The preparation method of the aramid nanofiber film-aerogel composite according to claim 5, characterized in that In the ANF / PVA / MXene / AgNWs mixed liquid, the mass fraction of ANF is 1-3%, the mass fraction of PVA is 0.2-0.6%, the mass fraction of MXene is 0.6-1%, and the mass fraction of AgNWs is 0.1-0.3%.

Citation Information

Cited By

  • Aerogel composite reinforced aramid fabric and preparation method thereof

    CN122235965A